2014
DOI: 10.1902/jop.2013.130361
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Influence of Interproximal Areas on Existence of Interdental Papillae

Abstract: The vertical and horizontal dimensions of interproximal areas had a substantial, independent, and combined effect on the existence of interproximal papillae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
0
14
0
4
Order By: Relevance
“…Additionally, the loss of marginal bone height can change the surrounding soft tissue architecture, resulting in the loss of interdental papilla and causing esthetic and phonetic changes and food impaction. 3 Decreases in inflammatory reactions, load concentrations, and bacterial leakage at the implantabutment interface are closely associated with marginal bone loss. 4,5 Material and methods.…”
mentioning
confidence: 99%
“…Additionally, the loss of marginal bone height can change the surrounding soft tissue architecture, resulting in the loss of interdental papilla and causing esthetic and phonetic changes and food impaction. 3 Decreases in inflammatory reactions, load concentrations, and bacterial leakage at the implantabutment interface are closely associated with marginal bone loss. 4,5 Material and methods.…”
mentioning
confidence: 99%
“…The IDD of the papilla was significantly narrower in the complete papilla group than in the deficient papilla group with the mean values of 2.07 mm and 1.81 mm, respectively (p < 0.05) ( Table 1). Results of some previous studies (Cho et al, 2006;Martegani et al, 2007;Kim et al, 2011;Kolte, Kolte & Mishra, 2014) suggested that the IDD is a significant predictor for papilla presence. However, data from other investigations reported that IDD was not a significant factor on multivariate analysis along with controlling for age and CP-BC (Chang, 2008;Chow et al, 2010;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Interdental papilla (IP), which occupies the interdental embrasure, not only acts as a barrier in protecting the periodontal structures, but also plays a critical role in facial esthetics (Chow et al, 2010;Chen et al, 2010;Kim et al, 2011). Preserving the gingival tissue in the embrasures of the maxillary anterior sextant is a key consideration in periodontal, restorative, and implant treatment (Tarnow, Magner & Fletcher, 1992;Kolte, Kolte & Mishra, 2014). Various factors may influence the presence or absence of the IP including the distance between underlying bone crest (BC) and contact point (CP), interdental distance (IDD), periodontal phenotype, and adjacent tooth form (Tarnow, Magner & Fletcher, 1992;Cho et al, 2006;Chen et al, 2010;Chow et al, 2010;Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The IDD of the papilla was significantly narrower in the complete papilla group than in the deficient papilla group with the mean values of 2.07 mm and 1.81 mm, respectively (p < 0.05) (Table 1). Results of some previous studies (Cho et al, 2006;Martegani, 2007;Kim et al, 2011;Kolte, Kolte, & Mishra, 2014) suggested that the IDD is a significant predictor for papilla presence.…”
Section: Discussionmentioning
confidence: 92%
“…Interdental papilla (IP), which occupies the interdental embrasure, not only acts as a barrier in protecting the periodontal structures, but also plays a critical role in facial esthetics (Chow et al, 2010;Chen et al, 2010;Kim et al, 2011). Preserving the gingival tissue in the embrasures of the maxillary anterior sextant is a key consideration in periodontal, restorative, and implant treatment (Tarnow, Magner, & Fletcher, 1992;Kolte, Kolte, & Mishra, 2014). Various factors may influence the presence or absence of the IP including the distance between underlying bone crest (BC) and contact point (CP), interdental distance (IDD), periodontal phenotype, and adjacent tooth form (Tarnow, Magner, & Fletcher, 1992;Cho et al, 2006;Chen et al, 2010;Chow et al, 2010;Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%